The impact of HBB‐related hemoglobinopathies carrier status on fetal fraction in noninvasive prenatal screening. (23rd March 2022) - Putra, Manesha; Kaseniit, Kristjan Eerik; Hicks, Melissa A.; Muzzey, Dale; Hackney, David
Abstract: Objective: We evaluated whether there is an association between β‐globin ( HBB ) pathogenic variants and fetal fraction (FF), and whether the association has a clinically relevant impact on non‐invasive prenatal screening (NIPS). Method: A whole‐genome sequencing NIPS laboratory database was retrospectively queried for women who underwent NIPS and carrier screening of both HBB and the α‐globin genes ( HBA1/HBA2 ). Women affected with either condition were excluded from the study, yielding a cohort size of 15, 853. A "corrected FF" was obtained via multivariable linear regression adjusted for the systematic impacts of maternal age, gestational age and BMI. Corrected FF distributions of HBB and HBA1/HBA2 carriers were each compared to non‐carriers using the Kolmogorov‐Smirnov test. Results: In this cohort, 291 women were carriers for HBB alone, and 1016 were carriers for HBA1/HBA2 alone. The HBB carriers had a lower corrected FF when compared to non‐carriers ( p < 0.0001). There was no difference in corrected FF among carriers and non‐carriers of HBA1/HBA2 . Conclusion: Carriers of pathogenic variants in the HBB gene, but not the HBA1/HBA2 genes, are more likely to have lower FF when compared to women with structurally normal hemoglobin. This decrease in FF could result in an elevated test‐failure rate if FF thresholds were used. Key points: What is already known about this topic? Multiple factors affect fetal fraction during noninvasive prenatal screening (NIPS), such as maternal BMI and gestational age. Patients affected with Hb beta chain‐related hemoglobinopathies have been shown to have lower fetal fraction during NIPS. What does this study add? This study demonstrates that HBB carriers—not just affected patients—also have lower fetal fraction on NIPS, adding to the literature of factors that could affect fetal fraction and NIPS performance.